A couple seated in the lalitasana posture on separate raised circular seats - Temples of India Project Team (Jio Institute, 2024)
Couples invoking shringara rasa (associated with romance, love, and attractiveness between lovers) are framed in panels with pillars and tiered shikhara with gavaksha (horseshoe) motifs. Unlike in other parts of the temple, the faces of the couples are not damaged and they are wearing heavy jewellery, elaborate headgear, and garments, indicating they belong to royalty. A couple in the lalitasana posture, sitting next to each other on separate raised circular seats. The central male figure is holding a flower in his right hand and his left hand is placed on his left leg. The central female figure is carrying a round fruit (or sweet) in her left hand and holding the man’s left hand with her right hand, showing affection. Two attendants are flanking the couple on either side. Flowering trees are drooping in the backdrop.